The Effect of STEM-Based Media on Students Scientific Literacy Skills in Reaction Rate Topic - Uni Sari; Gulmah Sugiharti (Universitas Lampung, 2026)
The Effect of STEM-Based Media to Improve Students Science Literacy Skills on the Reaction Rate Topic. This study aims to analyze the effect of using STEM (Science, Technology, Engineering, and Mathematics)-based learning media on improving students' scientific literacy. The method used was a quasi-experiment with a two-group Pretest-Postest design. The sample was selected through a purposive sampling technique, data were collected through a science literacy test instrument and analyzed using a t-test (α 0.05) and N-gain calculation. The results showed that the use of STEM-based media significantly improved students' scientific literacy with N-gain scores (0.7742) in the high category compared to the control class. It can be concluded that the integration of STEM-based virtual lab media is very feasible and effective as an innovative solution for visualizing complex chemical concepts. Based on the results of this study, it is recommended that the use of STEM media to optimize students' scientific competence in facing the development of science and technology